2019
DOI: 10.3390/nano9030381
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Combustion Nanocatalysts inside Solid Rocket Motor under Various Pressures

Abstract: In this paper, the dependences of the morphology, particle sizes, and compositions of the condensed combustion products (CCP) of modified double-base propellants (1,3,5-trimethylenetrinitramine (RDX) as oxidizer) on the chamber pressure (<35 MPa) and nickel inclusion have been evaluated under a practical rocket motor operation. It has been shown that higher pressure results in smaller average particle sizes of the CCPs. The CCPs of Ni-containing propellants have more diverse morphologies, including spherica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The presence of sulfur compounds as part of heterostructure matrices, such as SnS 2 /ZnInS 4 [ 28 ], CoTiO 3 /ZnCdS 2 [ 29 ], CdS/CeO 2 [ 30 ], CoWO 4 /CoS [ 31 ], and ZnCdS 2 /MoS [ 32 ], extend the light absorbance spectrum without solving the chemical stability issues in acid or alkaline environments. Composite materials based on g-C 3 N 4 [ 33 ], g-C 4 N 6 [ 34 ], and r-GO [ 35 ] exhibit high surface-active materials able to efficiently eliminate the pollutants using both absorption and photocatalytic processes.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of sulfur compounds as part of heterostructure matrices, such as SnS 2 /ZnInS 4 [ 28 ], CoTiO 3 /ZnCdS 2 [ 29 ], CdS/CeO 2 [ 30 ], CoWO 4 /CoS [ 31 ], and ZnCdS 2 /MoS [ 32 ], extend the light absorbance spectrum without solving the chemical stability issues in acid or alkaline environments. Composite materials based on g-C 3 N 4 [ 33 ], g-C 4 N 6 [ 34 ], and r-GO [ 35 ] exhibit high surface-active materials able to efficiently eliminate the pollutants using both absorption and photocatalytic processes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that many nanosized metals (Al, Mg, B, W, Zr, Ni, Cu, Fe, Ag, and Co) and metal oxides (e.g., Pb-, Cu-, Bi-, and Fe-based oxides) are widely used in solid propellants as fuels and the burning rate catalysts. , For instance, the nano-CuO and nano-Fe 2 O 3 have better catalytic effects than the microsized ones, , whereas the nano-Al can not only increase the energy content, but also enhance the burn rate of propellants with reduced pressure exponent under high pressure ranges . Furthermore, the thermal decomposition is the initial stage of combustion and explosion of materials, and the performance of thermal decomposition is an essential index that determines the combustion and explosion of materials. Therefore, the thermal behaviors and decomposition mechanisms of ICM-102 under the effects of nanosized metals and metal oxides must be investigated before the ICM-102 is applied in propellants.…”
Section: Introductionmentioning
confidence: 99%